Automatic Floor Cleaning Robot Using Arduino and Ultrasonic Sensor - Irawan, Yuda; Muhardi, Muhardi; Ordila, Rian; Diandra, Roni (Journal of Robotics and Control (JRC), 2021)
The entire floor cleaning robot is divided into several parts, namely consisting of an Ultrasonic Sensor, Motor Shield L298, Arduino Uno microcontroller, Servo, and Dc Motor. This tool works when the Arduino Uno microcontroller processes the ultrasonic sensor as a distance detector and a DC motor as a robot driver, then the DC motor is driven by the Motor Shield L298. When an ultrasonic sensor detects a barrier in front of it, the robot will automatically look for a direction that is not a barrier to the floor cleaning robot. The distance value on the sensor has been determined, that is, when the distance read by the ultrasonic sensor is below 15 cm. The results of testing the value of the ultrasonic sensor distance found different conditions that occur. In a distance of 15 cm, the condition of the prototype cleaning robot for the road floor cleaning is obtained, while the distance 15 cm, the condition for the prototype of the street floor cleaning robot has stopped.